Forest fragmentation and loss reduce richness, availability, and specialization in tropical hummingbird communities. (8th September 2017) - Hadley, Adam S.; Frey, Sarah J. K.; Robinson, W. Douglas; Betts, Matthew G.
Abstract: Hummingbirds are important pollinators of many native Neotropical plants but their abundance and diversity in landscapes dominated by intensive human uses such as agriculture have rarely been examined, despite such land‐uses prevailing in the tropics. We examined how tropical deforestation affects hummingbird community structure in premontane forest patches embedded in a tropical countryside of Coto Brus Canton, Costa Rica. We captured hummingbirds in fourteen landscapes representing a gradient in patch size and forest amount, and tested for the effects of these variables on (1) hummingbird captures at flowers (pollinator availability); (2) species richness; and (3) filtering of functional traits. After accounting for sampling effects, both hummingbird availability and species richness declined by 40% and 50%, respectively, across the gradient in deforestation that we observed (9–66% forest within 1000 m). Focal patch size was the strongest predictor, even after statistically accounting for the amount of forest and matrix composition of landscapes. These reductions in availability and richness were well predicted by functional traits; morphologically specialized species with the capacity to transport long‐distance outcrossed pollen and low functional redundancy within the pollinator network showed the greatest sensitivity to landscape change. We hypothesize that declines in hummingbird availability, diversity, and functional traits are important mechanisms driving the observed pollen limitation of ornithophilous flowers in fragmented tropical landscapes. Efforts to conserve large forest patches and enhance matrix permeability are critical for maintaining forest hummingbird communities and pollination services under current and predicted deforestation regimes.